Celebrating differences - Sunday, Star (Sunday Star, 2013)
INTERNATIONAL students from public and private institutions of higher education recently sang and danced their hearts out for a competition. The 1 World Culture event, cohosted by Nilai University and Universiti Putra Malaysia, is organised in collaboration with the Education Ministry and National Department for Culture and Arts (under the Tourism and Culture Ministry).